A critical overview of MXenes adsorption behavior toward heavy metals. (May 2022) - Othman, Zakarya; Mackey, Hamish R.; Mahmoud, Khaled A.
Abstract: In recent years, tremendous interest has been generated in MXenes as a fast-growing and diversified family of two-dimensional (2D) materials with a wide range of potential uses. MXenes exhibit many unique structural and physicochemical properties that make them particularly attractive as adsorbents for removing heavy metals from aqueous media, including a large surface area, abundant surface terminations, electron-richness, and hydrophilic nature. In light of the adsorption capabilities of MXenes at the ever-increasing rate of expansion, this review investigates the recent computational predictions for the adsorption capabilities of MXenes and the effect of synthesis of different MXene on their remediation behavior toward heavy metals. The influence of MXene engineering strategies such as alkalization, acidification, and incorporation into organic and inorganic hosts on their surface properties and adsorption capacity is compared to provide critical insights for designing effective MXene adsorbents. Additionally, the review discusses MXenes' adsorption mechanisms, the effect of coexisting ions on MXenes' selectivity, the regeneration of exhausted MXenes, and provides an overview of MXenes' stability and biocompatibility to demonstrate their potentiality for wastewater remediation. Finally, the review identifies current flaws and offers recommendations for further research. Graphical abstract: Image 1 Highlights: A comprehensive overview of MXene-based adsorbents for heavy metals removal is presented. The influence of MXenes engineering strategies on their surface characteristics and adsorption capacity are reviewed. Real applications of MXene-based adsorbents require in-depth understanding of their stability and toxicity. A road map for future research opportunities for MXene-based adsorbents is proposed.